Longitudinal extensive transverse myelitis as a neurological sequelae post-sea urchin stings: a case report - W M Izzuddin, Anas Aminin; Yusof Khan, Abdul Hanif Khan; Inche Mat, Liyana Najwa; Ahmad Apandi, Laila Mastura; Chia, Peck Kee; Basri, Hamidon (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2021)
Puncture injury from sea-urchin stings may lead to a local and systemic inflammatory reaction. We are reporting a case of longitudinal extensive transverse myelitis (LETM), which occurred ten days post-sea-urchin stings, where the patient presented with bilateral lower limb weakness. MRI showed multilevel segment spinal cord T2-weighted hyperintensity. Prompt intravenous methylprednisolone was administered, and the patient had a full recovery. To date, there is no case report of LETM associated with sea-urchin stings. Possible mechanism due to delayed immunological hypersensitivity to sea-urchin venom. This case demonstrates the potential serious neurological sequelae that may be associated with post-sea-urchin sting and the importance of prompt recognition and management in aiding recovery.